Pathogenesis of Leptospira - Azad Eshghi (Frontiers Research Topics, 2018)
The present eBook, consisting of a compilation of research and review articles, focuses on the features and mechanisms adopted and explored by pathogenic leptospires to successfully establish infection in the host. Additionally, this eBook provides information to support future work focused on the development of new prevention approaches against this important yet neglected zoonotic disease.